Pengaruh Komunikasi, Motivasi dan Reward terhadap Kinerja Karyawan PT. Wika Daerah Cilacap - Jajuk Herawati; Epsilandri Septyarini; Dewi Palupi (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study was to determine the effect of communication, motivation, and reward on the performance of employees of PT. Wika Cilacap Region. The meth-od used in this research is quantitative. Primary data was obtained from a question-naire with 51 respondents with a saturated sample technique. Then the data were ana-lyzed using descriptive analysis, multiple linear regression, t test (partial), F test (simul-taneous), and the coefficient of determination (R2). The results showed that communi-cation had no positive and insignificant effect on employee performance, motivation had no positive and insignificant effect on employee performance, reward had a posi-tive and significant effect on employee performance, and communication, motivation and simultaneous rewards had a positive and significant effect on performance. em-ployee. Keywords: Communication, Motivation, Reward, Employee Performance